EFEK LINGKUNGAN KERJA SOSIAL DAN KEPUASAN KERJA PADA LOYALITAS KARYAWAN DALAM INDUSTRI JASA PROPERTI - Maulana, Farhan; Sumiyati, Sumiyati; Razati, Girang (Business Education Program of Universitas Pendidikan Indonesia, 2019)
Abstract: The problem of employee loyalty is still the main concern in the company. It is because there are still many people researching for half a decade that the main components of loyalty include strong beliefs, acceptance of organizational goals, willing to mobilize considerable effort on behalf of the organization and a desire to maintain membership in the organization. Employees who have loyalty to their work will work more effectively and efficiently so that they can optimize their performance and produce good output in the form of products and services. Employee loyalty is a problem that almost happened in every type of company both services and manufacturing in various countries. Starting from the tourism industry, restaurant industry, education industry, health industry, and others. The low employee loyalty toward the company is characterized by decreasing performance, increasing attendance and employee turnover. This occurred to PT. Rezeki Jaya Makmur Sentosa in Ciamis, where the level of employee loyalty has decreased every year, especially in 2014-2018. Surely this is far from the expectations of companies that want their employees to have high loyalty. This study aims to determine (1) the influence of the social work environment on employee loyalty (2) the effect of job satisfaction on employee loyalty (3) the influence of the social work environment and job satisfaction on employee loyalty. This study uses a quantitative method involving 36 respondents using saturated sampling with data collection techniques using questionnaires. The data analysis technique used is multiple linear regression. The results of this study indicate that (1) the influence of the social work environment on employee loyalty partially influences by 70.6% (2) the effect of job satisfaction on employee loyalty partially influential by 63.3% (3) the influence of social work environment and job satisfaction on employee loyalty simultaneously influences by 73.5%. This shows that the better the social work environment and job satisfaction, the higher the employee loyalty. This means that if the social work environment and good job satisfaction will be obtained optimal work output, so that employee loyalty can increase properly.